Pengaruh The Theory of Planned Behavior terhadap Minat Beralih Menggunakan Kemasan Ramah Lingkungan - Muhammad Reynaldi; Ratni Prima Lita; Maruf (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to determine the intention to adopt green packaging at coffee shops in Padang City. This study uses the theory of planned behavior (TPB) to predict the intention of coffee shop entrepreneurs to use environmentally friendly packaging. The sample in this study is a coffee shop business actor who is not a national franchise in the city of Padang. The results of this study are expected to be able to find out how much coffee shop businesses in Padang City want to use environmentally friendly packaging. This is also expected to be able to reduce plastic waste in the city of Padang.